Constructions of race and childhood in facebook comments on online articles relating to child sexual abuse - Sumption, Nicola Jenni (My University, 2018)
Race, childhood and sexuality are three evocative concepts that often produce strong reactions when raised as topics of discussion, particularly in the context of South Africa’s history. Since the dawn of colonialism when human beings began to share space, race has been linked to certain stereotypical characteristics, and over time has also become both criminalised, and sexualised. Childhood, too, has also been linked with certain constructions, with children globally becoming linked to abstractions of purity, innocence and symbols of the health and wellbeing of the nation. Instances where children are abused, particularly in cases of sexual abuse, therefore provide an emotionally evocative landscape which is often representative of perceptions of morality on a broader scale. When the perpetrators and victims of these crimes become racialised, this landscape provides insights into constructions of race, and race relations within the country broadly, and that is the aim of the following research report. Facebook comments sections located on South African news articles reporting on cases of child sexual abuse have therefore been analysed using discourse analysis in order to better understand constructions of race and childhood where these two concepts intersect with sexual abuse. The following report details how these discourses reflect the deracialisation of childhood and the ways in which the discourse of childhood trumps that of race; the limits of childhood through analysis of an anomalous discourse in which the perpetrator was defended and the victims were blamed; and the racialization of sexuality -an exploration of the concept of a ‘culture of rape’, and the ways in which invisible whiteness is defended.
A resarch report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Community-Based Counselling Psychology at the University of the Witwatersrand, 2018
Keywords: Children--Social conditions; Racially mixed children; Child psychology